2012
DOI: 10.1111/j.1399-3062.2012.00747.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of mannose‐binding lectin‐2 polymorphism in the development of acute cellular rejection after transplantation for hepatitis C virus‐induced liver disease

Abstract: MBL-2 polymorphisms and gender are involved in the development of ACR after LT. CC genotype and gender match may be regarded as risk factors for ACR in HCV-positive graft recipients. Further studies are needed to confirm and verify this observation in non-HCV groups as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…Establishment of HCV infection is at least partly accomplished by successful escape from complement‐mediated effects, such as virus neutralization and lysis (Amet, Ghabril, Chalasani, & Byrd, ; Kim, Meyer, Di Bisceglie, & Ray, ). The involvement of the lectin pathway in hepatitis C has been demonstrated in different ways, mostly showing an effect of MBL deficiency with response to treatment (Eurich et al., ; Matsushita, Hijikata, & Ohta, ) and disease progression (Alves Pedroso et al., ; Eurich et al., ; Koutsounaki et al., ; Melo et al., ; MohammadHossein, Sara, Mohammad, Rasoul, & Ali, ; Segat et al., ). Possibly due to viral mechanisms of complement attenuation, higher levels of lectin pathway recognition proteins and of complement activation seem to be necessary in controlling HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Establishment of HCV infection is at least partly accomplished by successful escape from complement‐mediated effects, such as virus neutralization and lysis (Amet, Ghabril, Chalasani, & Byrd, ; Kim, Meyer, Di Bisceglie, & Ray, ). The involvement of the lectin pathway in hepatitis C has been demonstrated in different ways, mostly showing an effect of MBL deficiency with response to treatment (Eurich et al., ; Matsushita, Hijikata, & Ohta, ) and disease progression (Alves Pedroso et al., ; Eurich et al., ; Koutsounaki et al., ; Melo et al., ; MohammadHossein, Sara, Mohammad, Rasoul, & Ali, ; Segat et al., ). Possibly due to viral mechanisms of complement attenuation, higher levels of lectin pathway recognition proteins and of complement activation seem to be necessary in controlling HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Ficolin-2 and MBL were found to bind HCV envelope glycoproteins E1 and E2, activating complement against HCV-infected hepatocytes (Brown et al, 2010;Liu et al, 2009a,b), and MBL deficiency was repeatedly associated with HCV infection (Koutsounaki et al, 2008;Melo et al, 2009;Segat et al, 2007). Whereas early increased Ficolin-2 levels correlated with a better response to treatment (Hu et al, 2013), MBL deficiency was associated with no treatment response (Alves Pedroso et al, 2008;Eurich et al, 2012). Regarding MASP-2, Tulio et al (2011) investigated 104 South-Brazilian patients with chronic hepatitis C and found an association of homozygotes for the p.371D variant with susceptibility to HCV (OR = 6.33 [95%CI = 1.85-21.7], P = 0.003).…”
Section: Hepatitis C (Hcv)mentioning
confidence: 99%
“…Earlier, Munster et al [60] postulated a beneficial effect of donor's MBL2 X gene variant (promoter, position −221) on lung transplant outcome (better graft and BOS-free survival). However, carrying the same allele in hepatitis-C virus- (HCV-) positive recipients of liver transplants was a risk factor for acute cellular rejection [61]. …”
Section: Mbl In Injury To Peripheral Organsmentioning
confidence: 99%